Second Language Acquisition as a Mode-Switching Process An Empirical Analysis of Korean Learners of English - Song, Sooho (Palgrave Macmillan UK, 2018)
This book analyses processes of mode-switching in second language acquisition as they relate to Korean learners of English. In this empirical study, the author examines how native language influences and shapes usage of second language, particularly when the two are so dramatically different both in terms of grammar and the cultures in which they are anchored. Learning to speak English, she argues, entails switching from the formulaic to the strategic mode so that varying speaking norms and linguistic values are fully understood. This results in a mode switch towards the target culture. This intriguing book will be of interest to students and scholars of applied linguistics, sociolinguistics and English language education. Sooho Song is Assistant Professor of Foreign Languages and Literature at the University of Wisconsin-Milwaukee, USA. Her research interests focus on second language acquisition, applied linguistics, and Korean linguistics. Her publications include Politeness and Culture in Second Language Acquisition (Palgrave Macmillan, 2012) and articles in Language Sciences and Korea Journal. .